Filial Crisis and Erotic Politics in Black Cuban Literature : Daughters, Sons, and Lovers. - James, Conrad Michael (Monografías A Ser., 2019)
An affective reading of twentieth-century Afro-Cuban literature focussing on a set of concerns ranging from the filial to the erotic.